Study of Lavandula dentata, Salvia rosmarinus, and Cymbopogon citratus essential oils profile and antifungal activity of their mixture against the gray mold Botrytis cinerea - Chafiki, Salahddine; Oukarroum, Abdallah; Qessaoui, Redouan; El Assri, Soumaya; Alouani, Mohamed; Lahchimi, Hasnaa; El Arroussi, Hicham; Bouharroud, Rachid (Frontiers in Plant Science, 2025)
In this study, we investigated the chemical profile essential oils (EOs) extracted from Cymbopogon citratus, Salvia rosmarinus, and Lavandula dentata, as well as their antifungal activity against Botrytis cinerea in vitro and in vivo. GC–MS analysis showed that the EOs major components of C. citratus EOs were, Geranial (42.91%), Neral (34.11%), and β-Pinene (9.32%). While the S. rosmarinus major EOs components were Camphor (17.60%), α-Pinene (14.39%), and 1,8-cineol (14.13%). Contrariwise L. dentata EOs, Camphor (33.95%), 1,8-cineol (32.35%), and β-Pinene (5.23%) were the predominant compounds. Regarding the in vitro antifungal activity, the EOs of three plants inhibited the mycelial growth of B. cinerea in a dose-dependent manner. Moreover, at the concentration of 0.32 µL/mL air, all EOs demonstrated the inhibition of the mycelia growth of B. cinerea. In addition, the combination of EOs increased the antifungal activity of B. cinerea compared to their individual application. According to simplex-centroid design analysis, the most efficient antifungal of the mixture of EOs extracted from L. dentata, S. rosmarinus, and C. citratus was noted EOs at a ratio (1:1:1). This mixture inhibited the mycelial growth at 1.6 µL/mL, with IC50 and IC90 value of 0.46 µL/mL and 0.81 µL/mL, respectively. In addition, in vivo tests showed that this EOs mixture significantly reduced the decay of cherry tomatoes caused by B. cinerea with an average of 88.37%. Also, the disease severity value recorded for the plant treated with the EOs mixture was 19.29% compared to the control with an average of 88.57%. This study demonstrates that the mixture of L. dentata, S. rosmarinus, and C. citratus EOs is a promising natural antifungal agent for managing B. cinerea infections.